2019
DOI: 10.1002/jhbp.675
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of common bile duct stones following laparoscopic common bile duct exploration: a multicenter study

Abstract: Background Recurrence of common bile duct stone (CBDS) is not common after laparoscopic common bile duct exploration (LCBDE). This study aimed to investigate the risk factors of recurrence of CBDS after LCBDE. Methods Patients who underwent LCBDE between January 2001 and December 2018 in four teaching hospitals of The Catholic University of Korea were included. The operation, fluoroscopy, and endoscopic retrograde cholangiopancreatography records were investigated retrospectively. The primary outcome of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
(34 reference statements)
3
20
1
Order By: Relevance
“…In comparison to patients treated with surgery on other abdominal organs, a higher percentage of biliary surgery patients need subsequent surgery, which may have a substantial physical and psychological effect on patients and is a significant medical burden [ 8 , 9 ]. Duodenal diverticulum [ 10 ], common bile duct dilatation [ 11 ], and surgical injury to the common bile duct [ 12 ] are all factors that impact recurrent common bile duct stones following biliary surgery. Age, gender, heredity, metabolism, dietary habits, and obesity, according to other research, may all have a role in the recurrence of common bile duct stones following biliary surgery [ 2 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to patients treated with surgery on other abdominal organs, a higher percentage of biliary surgery patients need subsequent surgery, which may have a substantial physical and psychological effect on patients and is a significant medical burden [ 8 , 9 ]. Duodenal diverticulum [ 10 ], common bile duct dilatation [ 11 ], and surgical injury to the common bile duct [ 12 ] are all factors that impact recurrent common bile duct stones following biliary surgery. Age, gender, heredity, metabolism, dietary habits, and obesity, according to other research, may all have a role in the recurrence of common bile duct stones following biliary surgery [ 2 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This function is also lost when the gallbladder is removed. Park et al (65) showed a prior history of cholecystectomy can increase the risk recurrence of choledocholithiasis after LCBDE and reported that prophylactic cholecystectomy was not required to prevent recurrence of choledocholithiasis in Asian populations without stones after ERCP stone removal. YOO et al (96) found that cholesterol stones were a risk factor for the recurrence of choledocholithiasis after cholecystectomy.…”
Section: Endoscopic Nasobiliary Drainage (Enbd) and Saline Preventivementioning
confidence: 99%
“…(25,55) However, a large number of follow-up observations showed that the recurrence rate of common bile duct stone after endoscopic treatment was 4%-25%. (60,65) Choledocholithiasis may cause acute suppurative cholangitis, pancreatitis, biliary perforation, etc. The recurrent factors of choledocholithiasis are complex and cannot be explained by a single factor.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the clearance rates of one-stage LCBDE + LC (91.3%) and two-stage EST + LC (95.6%) were similar to those reported in a previous study. Long-term follow-up studies have reported, that CBD stones recur in approximately 2.1% to 13.5 % of cases after LCBDE and 7.5% to 9.5 % of cases after EST [ 19 21 ]. In the present study, recurrence rates of CBD stones after LCBDE or EST were 4.3% and 8.8%, respectively, which are similar to those of previous studies.…”
Section: Discussionmentioning
confidence: 99%